Great Purple Hairstreak; Great Blue Hairstreak Atlides halesus (Cramer) (Insecta: Lepidoptera: Lycaenidae) - Don W. Hall (EDIS, 2021)
The great purple hairstreak, Atlides halesus (Cramer), is one of our most beautiful and fascinating southern butterflies. Although its preferred and most frequently used common name is great purple hairstreak (Miller 1992), it does not have any true purple coloring on it. A few publications (Gerberg & Arnett 1989, Emmel 1975, Pyle 1981) use the name great blue hairstreak which is more appropriate.